2016
DOI: 10.1093/nar/gkw068
|View full text |Cite
|
Sign up to set email alerts
|

The ISW1 and CHD1 ATP-dependent chromatin remodelers compete to set nucleosome spacingin vivo

Abstract: Adenosine triphosphate-dependent chromatin remodeling machines play a central role in gene regulation by manipulating chromatin structure. Most genes have a nucleosome-depleted region at the promoter and an array of regularly spaced nucleosomes phased relative to the transcription start site. In vitro, the three known yeast nucleosome spacing enzymes (CHD1, ISW1 and ISW2) form arrays with different spacing. We used genome-wide nucleosome sequencing to determine whether these enzymes space nucleosomes different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
241
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(263 citation statements)
references
References 64 publications
9
241
0
Order By: Relevance
“…This resonates with in vivo derived notions that remodelers are important for nucleosome positioning (Badis et al, 2008; Ganguli et al, 2014; Gkikopoulos et al, 2011; Hartley and Madhani, 2009; Ocampo et al, 2016; Parnell et al, 2008; van Bakel et al, 2013), via dynamic competition of different remodeling activities (Ganguli et al, 2014; Ocampo et al, 2016; Parnell et al, 2015; Yen et al, 2012), but now establishes their direct, specific and sufficient contributions.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This resonates with in vivo derived notions that remodelers are important for nucleosome positioning (Badis et al, 2008; Ganguli et al, 2014; Gkikopoulos et al, 2011; Hartley and Madhani, 2009; Ocampo et al, 2016; Parnell et al, 2008; van Bakel et al, 2013), via dynamic competition of different remodeling activities (Ganguli et al, 2014; Ocampo et al, 2016; Parnell et al, 2015; Yen et al, 2012), but now establishes their direct, specific and sufficient contributions.…”
Section: Discussionsupporting
confidence: 56%
“…Inasmuch as different remodelers have distinct remodeling activities (Bartholomew, 2014), the relative amounts added were based on ATPase activity units, which all remodelers have in common. Similar to the respective in vivo phenotype (Gkikopoulos et al, 2011; Ocampo et al, 2016), this mutant extract failed to form well-aligned arrays (Figures 1A and 1B, graphs 3 vs. 4), although NFRs and +1 nucleosomes were largely reconstituted but with somewhat less accuracy (peak position, Figure 1C, Table S1) and precision (positioning strength, Table S2). Thus, formation of the NFR and +1 nucleosome is biochemically separable from array formation/alignment, and the former can be achieved in extracts without ISW1/2/Chd1 remodelers.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…To facilitate comparison between different datasets, we used a common template trueβ^α/j for all three datasets. This common template was constructed by combining average nucleotide frequencies of nucleosomes detected by MNase-seq [39] and chemical cleavage [40]; combining these two types of data help eliminate potential MNase digestion biases towards the ends of the nucleosome as well as chemical cleavage biases around the nucleosome dyad (Fig. S8 of Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
“…S12 of Supplementary Material), suggesting that CEM was consistently underestimating the nucleosome number in these datasets (Table S5 of Supplementary Material). Visually comparing predicted and observed nucleosome occupancy profiles showed that, for datasets where nucleosome number was significantly underestimated ( Kaplan-MNase-invivo-WT [3] and Ocampo-MNaseinvivo-WT [39]), CEM-predicted nucleosome occupancy was indeed missing a large fraction of nucleosomes evident from experimental data (Fig. S13 of Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%